2014
DOI: 10.1128/aem.00140-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Malic Enzyme during Fatty Acid Synthesis in the Oleaginous Fungus Mortierella alpina

Abstract: The generation of NADPH by malic enzyme (ME) was postulated to be a rate-limiting step during fatty acid synthesis in oleaginous fungi, based primarily on the results from research focusing on ME in Mucor circinelloides. This hypothesis is challenged by a recent study showing that leucine metabolism, rather than ME, is critical for fatty acid synthesis in M. circinelloides. To clarify this, the gene encoding ME isoform E from Mortierella alpina was homologously expressed. ME overexpression increased the fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
142
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(145 citation statements)
references
References 36 publications
2
142
1
Order By: Relevance
“…Many enzymes can generate NADPH; however, their relative contributions to lipogenesis are still unclear. We have previously shown that ME1 overexpression increases total fatty acid production whereas ME2 facilitates fatty acid desaturation (5,8). This finding suggests that various sources of NADPH may play different roles during fatty acid synthesis and that the simultaneous overexpression of cytosol-and membrane-type NADPH-producing enzymes would augment the levels of total fatty acids as well as their desaturation.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Many enzymes can generate NADPH; however, their relative contributions to lipogenesis are still unclear. We have previously shown that ME1 overexpression increases total fatty acid production whereas ME2 facilitates fatty acid desaturation (5,8). This finding suggests that various sources of NADPH may play different roles during fatty acid synthesis and that the simultaneous overexpression of cytosol-and membrane-type NADPH-producing enzymes would augment the levels of total fatty acids as well as their desaturation.…”
Section: Discussionmentioning
confidence: 85%
“…The genes g6pd1, g6pd2, g6pd3, pgd, and idh1 from M. alpina were overexpressed in the same organism. Two pairs of previously described specific primers (HisproF1/TrpCR1 and HisproF2/ TrpCR2) ( Table 1) were applied to confirm the presence of the integrated transfer DNA (T-DNA) in the genomic DNA of transformants (1,5,8). Expression levels, enzymatic activities, NA-DPH, and fatty acid levels were analyzed in three replicates of each transformed strain, including ME1 (malE1)-and ME2 (malE2)-overexpressing strains that were previously constructed (5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations